2007
DOI: 10.1103/physrevlett.99.054502
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Dispersivity of Randomly Packed Monodisperse Spheres

Abstract: We determine the intrinsic longitudinal dispersivity l(d) of randomly packed monodisperse spheres by separating the intrinsic stochastic dispersivity l(d) from dispersion by unavoidable sample dependent flow heterogeneities. The measured l(d), scaled by the hydrodynamic radius r(h), coincide with theoretical predictions [Saffman, J. Fluid Mech. 7, 194 (1960)] for dispersion in an isotropic random network of identical capillaries of length l and radius a, for l/a=3.82, and with rescaled simulation results [Maie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 23 publications
3
37
0
Order By: Relevance
“…In general, carbonate rocks are characterized as a more heterogeneous media than sandstone rocks and therefore require a longer time to reach the asymptotic regime. Recently, there have been extensive studies on pre-asymptotic dispersion in various porous media (Bijeljic et al, 2011(Bijeljic et al, , 2013aBijeljic et al, 2013b;Blunt et al, 2013;Mitchell et al, 2008;Scheven et al, 2007;Scheven et al, 2005). Most of these focused on velocities in the transition region or above is Fickian-like and predominately dictated by restricted diffusion (Bijeljic et al, 2004;Gist et al, 1990;Levy and Berkowitz, 2003;Sahimi, 1995).…”
Section: Asymptotic and Preasymptotic Regimes In Porous Mediamentioning
confidence: 99%
“…In general, carbonate rocks are characterized as a more heterogeneous media than sandstone rocks and therefore require a longer time to reach the asymptotic regime. Recently, there have been extensive studies on pre-asymptotic dispersion in various porous media (Bijeljic et al, 2011(Bijeljic et al, , 2013aBijeljic et al, 2013b;Blunt et al, 2013;Mitchell et al, 2008;Scheven et al, 2007;Scheven et al, 2005). Most of these focused on velocities in the transition region or above is Fickian-like and predominately dictated by restricted diffusion (Bijeljic et al, 2004;Gist et al, 1990;Levy and Berkowitz, 2003;Sahimi, 1995).…”
Section: Asymptotic and Preasymptotic Regimes In Porous Mediamentioning
confidence: 99%
“…Such difference may be attributed to quite limited explored length scales, so that some macroscale effects responsible for higher macroscale dispersivity may be missed. Besides, from MRI (Magnetic Resonance Imaging) of D 2 O injection in chromatography gel columns a significant band broadening due to column inlet was observed [12], and from an analysis of NMR data, it was suggested that imperfect flow injection could also have a significant impact on the dispersion observed from breakthrough curve experiments [22]. This work also showed that a further analysis of PFG data makes it possible to distinguish intrinsic dispersion, which appears to be in agreement with the theoretical prediction for a random network of capillaries [23], whose resulting D is below the master curve (see above) by a factor about 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant scatter exists. The scatter may be caused by the difference of the pore geometry and the flow heterogeneities during the solute injection process in different experiments (Scheven et al, 2007). The packing method, wall confinement, particle size and shape distributions all may influence the pore geometry.…”
Section: Introductionmentioning
confidence: 99%
“…The scatter hinders our accurate understanding of the dispersion behavior. Recently, an important advancement has been made (Scheven et al, 2007(Scheven et al, , 2014Scheven, 2013). The longitudinal (Scheven et al, 2007(Scheven et al, , 2014 and transverse (Scheven, 2013;Scheven et al, 2014) dispersion coefficients for random particle packs were obtained by nuclear magnetic resonance (NMR) based experiments and the dispersion coefficients for columns with different pore geometries collapsed into the same value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation